Analysis and design of UI and UX of the Taring application using goal-directed design and cognitive walkthrough methods - Tiyasa, Abyudaya; Wirdiani, Ni Kadek Ayu; Rusjayanthi, Ni Kadek Dwi (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2023)
Taring is a web-based application used for online administrative services for both Indonesian citizens and foreign nationals in the field of population administration. It is published by the Denpasar Population and Civil Registration Office. The taring application was released on June 8, 2020, and includes features such as managing Family Cards, e-IDs, Change of Residence Letters, and Legalization. Analysis and evaluation of the Taring application are necessary to improve usability, quality of use, and the provided information. This is achieved through the utilization of the Goal-Directed Design method and the Cognitive Walkthrough method in its process. The employed analysis and design method is Goal-Directed Design, which focuses on designing and developing interactive systems to make them more useful, with a focus on the diverse goals of the users. The evaluation methods used are the Cognitive Walkthrough and the System Usability Scale questionnaire, which assess usability and the application's usage based on observations of the users. The results of the Cognitive Walkthrough testing revealed 20 issues related to user interface and user experience, while the research findings indicated an increase in effectiveness and efficiency. The research also demonstrated an improvement in usability using the System Usability Scale method, with the score rising from 50.8 (E) to 88.9 (A).